KORELASI KEBERSIHAN BOTOL SUSU DENGAN KEJADIAN INFEKSI SALURAN PERNAFASAN AKUT (ISPA) PADA BAYI USIA 1-12 BULAN - Hariyanto Hariyanto; Eliya Rohmah; Dinar Ratna Wahyuni (Jurnal Delima Harapan, 2018)
Acute Respiratory Infection is an acute infection involving upper respiratory tract and lower respiratory tract. This infection is causedby viruses, fungi and bacteria. At the end of 2000, ISPA reached 6 cases among 1000 babies and toddlers. In 2003, cases of infant mortality due to ISPA as many as 5 out of 1000 children under five. This study aimed at determining the relationship of Cleaning the Milk Bottle With Acute Respiratory Infection Incidence. The research design was analytical method with cross sectional approach. The population was 57 people and sample size was 30 respondents who had infants during January - April 2017 who got acute respiratory infection. The sampling technique was Accidental sampling. Data of cleaning milk bottle were collected by interviewing mothers who had babies 1-12 months while data of the incidence of acute respiratory infection based on medical record of respondens. Data scored and analyzed by spearman rank statistical test. Based on result of research got 46,7% or 14 responden, the cleaning of milk bottle were less cathegory and 73,3% or 22 respondens had acute respiratory infection. Result of statistic test showed ρ ≤ 0,05. the ρ value = 0,000. It was concluded H˳ refused and Hı accepted which mean there was correlation between the cleaning milk bottle with the incidence of acute respiratory infection at infant. The researcher suggested to health workers and mothers to pay more attention to health care for their babies and the environment.